Epidemiological evaluation of the outcomes of initial root canal therapy in permanent teeth of a publicly insured paediatric population. Issue 5 (31st March 2022) - Burns, Lorel E.; Terlizzi, Kelly; Solis‐Roman, Claudia; Wu, Yinxiang; Sigurdsson, Asgeir; Gold, Heather T.
Abstract: Background: Previously published epidemiological outcome studies of nonsurgical root canal therapy (NSRCT) in the United States utilize data only from a single, private dental insurer for adult populations. Aim: This study aimed to investigate the outcomes of initial NSRCT, performed on permanent teeth, in a publicly insured paediatric population. Design: New York State Medicaid administrative claims were used to follow 77 741 endodontic procedures in 51 545 patients aged 6–18, from the time of initial NSRCT until the occurrence of an untoward event (retreatment, apicoectomy, and extraction). The initial treatment and untoward events were identified by Current Dental Terminology codes. The Kaplan–Meier survival estimates were calculated at 1, 3, and 5 years. Hazard ratios for time to permanent restoration and restoration type were calculated using the Cox proportional hazards model. Results: The median follow‐up time was 44 months [range: 12–158 months]. Procedural, NSRCT, survival was 98% at 1 year, 93% at 3 years, and 88% at 5 years. Extraction was the most common untoward event. Teeth permanently restored with cuspal coverage had the most favorable treatment outcomes. Conclusions: Overall, 89% of teeth were retained and remained functional over a minimum follow‐up time of 5 years. These results elucidate the expected outcomes of NSRCT in permanent teeth for paediatric patients with public‐payer dental benefits.